2010
DOI: 10.1159/000321819
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bet v1, Bet v2 and Bet v4 Specific IgE Antibodies in the Sera of Children and Adult Patients Allergic to Birch Pollen: Evaluation of Different IgE Reactivity Profiles Depending on Age and Local Sensitization

Abstract: Background: Birch pollen belongs to the major allergen triggers in the spring season in Europe. Our rapidly expanding knowledge of the allergenic molecules enables us to better recognize the individual differences between the reactivity of specific IgE antibodies of individual patients and allergic populations living in various regions of the world. Method: In a group of birch pollen-allergic patients living in the Czech Republic (107 children, 71 adults) we detected the presence of Bet v1, Bet v2 and Bet v4 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 48 publications
1
16
1
1
Order By: Relevance
“…The first part of the present study showed a significant gradient of sensitization across Italy for all birch allergens, thus confirming findings from previous studies [19][20][21][22]. The findings for Genoa in particular, in terms of both sensitization profile and prevalence of OAS, are surprising.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The first part of the present study showed a significant gradient of sensitization across Italy for all birch allergens, thus confirming findings from previous studies [19][20][21][22]. The findings for Genoa in particular, in terms of both sensitization profile and prevalence of OAS, are surprising.…”
Section: Resultssupporting
confidence: 91%
“…An intriguing gradient of sensitization across Europe has been reported: Bet v 1 is predominant in northern Europe, whereas Bet v 2 and Bet v 4 are more relevant in southern Europe [19][20][21][22]. Therefore, this study aimed to evaluate the profile of sensitization to birch allergen molecules in a large sample of allergic patients in Italy by taking into consideration the geographic area and the presence of associated OAS.…”
Section: Introductionmentioning
confidence: 99%
“…Huş ağacı polenlerindeki allerjenlerin belirlenmesine yönelik yapılan çalışmada Betula pendula (=Betula verrucosa) türünde 9-35 kDa arasında allerjenler (Bet v 1-7) saptanmıştır (11,(64)(65)(66)(67)(68)(69)(70). Huş ağacı polen duyarlılığı bulunan hastaların %90'nından fazlasında majör allerjen Bet v 1 allerjenidir (71). Betula poleninde allerjenler özellikle sitoplazmada amiloplastlarda, polen duvarında ve por kenarlarında yerleşmişlerdir (72)(73)(74) (93).…”
Section: Discussionunclassified
“…This finding is in agreement with results of several other studies. Sekerkova and Polackova [3] stated that the prevalence of Bet v 1-, Bet v 2- and Bet v 4-specific IgE in birch pollen-allergic individuals is dependent not only on the region in which they live but also on their age. Mediaty and Neuber [25] found that total and allergen-specific serum IgE decreases with age in patients with allergic rhinitis and asthma but not in patients with atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, epidemiological studies have shown an increasing prevalence of IgE-mediated allergy and nowadays up to 25% of the European population suffer from some form of atopic diseases [2,3]. In Africa the prevalence of atopic dermatitis, asthma and allergic rhinitis has also been increasing over the past decades [4].…”
Section: Introductionmentioning
confidence: 99%